ANALYZING THE INFLUENCE OF ADVERTISING AND OUTDOOR MEDIA ON PRISM CEMENT LTD.’S MARKET PERFORMANCE IN SATNA - Chhabariya, Kiran; Singh, Chandan; Soni, Kartik; Garg, Ankit Kumar; Tripathi, Shivam Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of advertising and outdoor media on Prism Cement Limited’s market performance in Satna. The research employs both qualitative and quantitative methods to analyze how advertising strategies and outdoor media campaigns contribute to brand visibility, customer engagement, and market share for Prism Cement Limited. Through surveys, interviews, and financial analysis, the study aims to uncover correlations between advertising expenditures, media channels utilized, and market performance indicators such as sales growth and brand recognition. The findings suggest significant insights into effective marketing strategies for the cement industry in regional markets like Satna, offering practical implications for marketers and managers aiming to enhance their company’s market performance through strategic media investments.